2016
DOI: 10.1090/mcom/3122
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-unbiased Hadamard matrices and weakly unbiased Hadamard matrices: A coding-theoretic approach

Abstract: This paper is concerned with quasi-unbiased Hadamard matrices and weakly unbiased Hadamard matrices, which are generalizations of unbiased Hadamard matrices, equivalently unbiased bases. These matrices are studied from the viewpoint of coding theory. As a consequence of a coding-theoretic approach, we provide upper bounds on the number of mutually quasi-unbiased Hadamard matrices. We give classifications of a certain class of self-complementary codes for modest lengths. These codes give quasi-unbiased Hadamard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…In Section 6, we deal with real spherical 3-distance sets related to Hadamard matrices and association schemes. We improve the known upper bounds obtained by the linear programming in [1] and reprove a result in association schemes.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In Section 6, we deal with real spherical 3-distance sets related to Hadamard matrices and association schemes. We improve the known upper bounds obtained by the linear programming in [1] and reprove a result in association schemes.…”
Section: Introductionmentioning
confidence: 71%
“…(b) and A the adjacency matrix of the tournament attached to X. Then the Gram matrix of X is the same as the Gram matrix of the image of the minimal representation of the tournament [12,Theorem 4.8 (ii)], and the Gram matrix of X is given by (1) [12,Theorem 3.1 (3)]. After the suitable permuting the rows and the columns simultaneously the matrix (…”
Section: Complex 2-codesmentioning
confidence: 99%
“…Using this equality, it is easily shown that for weighing matrices W 1 , W 2 of order n and weight k, W 1 , W 2 are quasi-unbiased for parameters (n, k, l, a) if and only if (1/ √ a)W 1 W ⊤ 2 is a (0, 1, −1)-matrix. The case for the parameters (n, n, l, a) was studied in [2] from the viewpoint of coding theory.…”
Section: Preliminariesmentioning
confidence: 99%
“…It is known that if there exist Hadamard matrices of order 4m, 4n, then there exists a Hadamard matrix of order 8mn [1]. This construction was used to construct quasi-unbiased Hadamard matrices in [2]. We use this idea to orthogonal designs in order to obtain unbiased orthogonal designs.…”
Section: Proof Straightforwardmentioning
confidence: 99%
See 1 more Smart Citation